Environmental filtering controls soil biodiversity in wet tropical ecosystems. (March 2022) - Cui, Haiying; Vitousek, Peter M.; Reed, Sasha C.; Sun, Wei; Sokoya, Blessing; Bamigboye, Adebola R.; Verma, Jay Prakash; Mukherjee, Arpan; Peñaloza-Bojacá, Gabriel F.; Teixido, Alberto L.; Trivedi, Pankaj; He, Ji-Zheng; et al.
Abstract: The environmental factors controlling soil biodiversity along resource gradients remain poorly understood in wet tropical ecosystems. Aboveground biodiversity is expected to be driven by changes in nutrient availability in these ecosystems, however, much less is known about the importance of nutrient availability in driving soil biodiversity. Here, we combined a cross-continental soil survey across tropical regions with a three decades' field experiment adding nitrogen (N) and phosphorus (P) (100 kg N ha −1 y −1 and 100 kg P ha −1 y −1 ) to Hawai'ian tropical forests with contrasting substrate ages (300 and 4, 100, 000 years) to investigate the influence of nutrient availability to explain the biodiversity of soil bacteria, fungi, protists, invertebrates and key functional genes. We found that soil biodiversity was driven by soil acidification during long-term pedogenesis and across environmental gradients, rather than by nutrient limitations. In fact, our results showed that experimental N additions caused substantial acidification in soils from Hawai'i. These declines in pH were related to large decreases in soil biodiversity from tropical ecosystems in four continents. Moreover, the microbial activity did not change in response to long-term N and P additions. We concluded that environmental filtering drives the biodiversity of multiple soil organisms, and that the acidification effects associated with N additions can further create substantial undesired net negative effects on overall soil biodiversity in naturally tropical acid soils. This knowledge is integral for the understanding and management of soil biodiversity in tropical ecosystems globally. Graphical abstract: Results of SEMs identify the direct and indirect relationships between the diversity of soil organisms and N and P additions, and soil substrate ages in Hawai'i experiments (a-c) and tropical ecosystems in four continents (d-f). The diversity (OTU number, richness) of soil organisms includes bacteria, fungi, and protists. The variance explained by the model ( R 2 ) of each parameter is given. R 2 conditional denotes the proportion of variance explained by the included predictors without accounting for random effects of country/site. R 2 marginal denotes the proportion of variance explained by the included predictors by accounting for random effects of country/site. Grey dashed arrows represent non-significant relationships in the models, which, however, improved the model fit when used ( p  > 0.05). Other non-significant SEM arrows were removed from the model to improve the model fit. Avail N, available N; Avail P, available P; MAP, mean annual precipitation; MAT, mean annual temperature; RMSEA, root mean square error of approximation. * P  < 0.05, ** P  < 0.01 and *** P  < 0.001. Image 1 Highlights: Biodiversity is driven more by soil acidification more than, nutrient limitation in a Hawai'i long-term, cross-site experiment. Negative effects of soil acidification on biodiversity are stronger in old, more weathered soils. Microbial diversity and microbial activity had contrasting responses to N and P additions. pH was positively correlated with biodiversity in tropical soils across continents.